Suppressive action of samorin on the cyclical development of pathogenic trypanosomes in Glossina morsitans centralis - Moloo, S.K.; Kamunya, G.W. (Wiley, 1987)
Male Glossina sexually sterilized by gamma‐irradiation are as efficient vectors of trypanosomiasis as fertile males. An attempt was made, using isometamidium chloride (Samorin), to interfere with the cyclical development of trypanosomes in sterile males, destined for use in the sterile insect release (SIR) method of tsetse eradication. The infection rate with mature Trypanosoma congolense Broden was effectively reduced in sterile male Glossina morsitans centralis Machado, when the flies were fed on an infected goat 2 days after they were fed as tenerals on an in vitro bloodmeal containing 8 μg Samorin/ml blood. The infection rates with mature T. vivax Ziemann and T. brucei brucei Plimmer & Bradford were completely suppressed at this drug dose. When sterile teneral males were fed on a bloodmeal containing 12 fig/m Samorin and given the infected bloodmeal 10 days later, infections by mature T. vivax, T. congolense and T.b.brucei were completely suppressed. Hence in the management of a tsetse eradication programme utilizing the SIR method, it is recommended that the sterile teneral male tsetse should, prior to release, be given a bloodmeal containing Samorin at 12–15 μg/ml blood. This will effectively suppress future disease transmission.